Determination of Surface Acidity on The Natural and Synthetic Montmorillonite Clays by Titration Method - Sekewael, Serly J. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Determination of surface acidity on the natural and synthetic montmorillonite clays has been carried out using the acid-base titration method to count the number of bound acid sites per gram of clay. The total acidity of natural and synthetic montmorillonite surfaces obtained was 4.67 and 5.33 mmol/g, respectively. FTIR analysis results indicate the presence of functional groups from the tetrahedral and octahedral constituents. Both samples have similar absorption patterns. The similarity of absorption patterns was followed by a decrease in intensity and shift in some absorption bands, and the appearance of new absorption bands.